ETC L2 ARCHIVE from Norunda, 2018–2025 - Natascha Kljun; Meelis Molder; Irene Lehner; Gunnar Bergström; Anders Båth; Jutta Holst; Maj-Lena Linderson (Integrated Carbon Observation System, 2026)
Archive Product for ICOS Ecosystem data. It is the most complete data collection for the ICOS ecosystem station and it contains all the data (continuous fluxes and meteo and ancillary) and metadata collected and produced.
Kljun, N., Molder, M., Lehner, I., Bergström, G., Båth, A., Holst, J., Linderson, M. (2026). ETC L2 ARCHIVE from Norunda, 2018–2025, ICOS RI, https://hdl.handle.net/11676/DDvxJ-2OoBO44AGePSxpN8-2
Keywords: Ecosystem Thematic Centre; ICOS; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap